(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Niger seed has several health advantages. The Niger seed is used commercially for oil and as bird feed. In this study, we used Niger seed as Whole Niger Seed Flour (WNSF) and Roasted Niger Seed Flour (RNSF) (15%, 30%, and 45%) partially replaced by refined wheat flour in cookies. We examined the effect of fortified on cookies with Niger seed on the physical and sensory characteristics. We prepared two types of cookies sample with different blends, WNSF with blends (C1= 15%, C2= 30%, and C3 =45%) and RNSF with blends (RC1= 15, RC2= 30% and RC3= 45%) with Control sample (C0). In this study, we found that when we prepared cookies sample with (Whole / Roasted flour) simultaneously increasing order; spread ratio, hardness, and color showed increasing order and water absorption content, and gluten showed decreasing order and decreasing sensory attribute with increasing composite flour because of the bitter taste.